2005
DOI: 10.1002/hipo.20097
|View full text |Cite
|
Sign up to set email alerts
|

A natural form of learning can increase and decrease the survival of new neurons in the dentate gyrus

Abstract: Granule cells born in the adult dentate gyrus undergo a 4-week developmental period characterized by high susceptibility to cell death. Two forms of hippocampus-dependent learning have been shown to rescue many of the new neurons during this critical period. Here, we show that a natural form of associative learning, social transmission of food preference (STFP), can either increase or decrease the survival of young granule cells in adult rats. Increased numbers of pyknotic as well as phospho-Akt-expressing Brd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
54
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(57 citation statements)
references
References 60 publications
2
54
0
1
Order By: Relevance
“…Although the mechanism of increased survival may not be the same, some forms of hippocampus-dependent learning tasks during this same period were reported to increase the survival of new neurons (Gould et al, 1999;Olariu et al, 2005). A critical period for the survival of new neurons in the olfactory bulb, another region associated with adult neurogenesis, was found during the third and fourth weeks after neuronal birth (Yamaguchi and Mori, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanism of increased survival may not be the same, some forms of hippocampus-dependent learning tasks during this same period were reported to increase the survival of new neurons (Gould et al, 1999;Olariu et al, 2005). A critical period for the survival of new neurons in the olfactory bulb, another region associated with adult neurogenesis, was found during the third and fourth weeks after neuronal birth (Yamaguchi and Mori, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…However, the direction of the effect is not always the same. For example, it has been shown that training with trace eyeblink conditioning, spatial learning in the Morris water maze and conditioned food preference increase the number of newborn cells in the DG of adult rats (Gould et al, 1999c;Ambrogini et al, 2000;Lemaire et al, 2000;Dobrossy et al, 2003;Leuner et al, 2004c;Hairston et al, 2005;Olariu et al, 2005). These effects appear to be specific to learning that requires the hippocampus.…”
Section: Evidence In Favormentioning
confidence: 99%
“…Olariu et al (2005) have shown that the amount or number of training trials that an animal is exposed to determines whether the effect on adult neurogenesis is positive or negative. Applying this interpretation to the larger literature on this subject, it seems that fewer training trials have been associated with enhanced cell survival whereas a greater number of trials have been associated with no effect or decreases in survival (Gould et al, 1999c;Dobrossy et al, 2003;Ambrogini et al, 2004a;Olariu et al, 2005;Snyder et al, 2005). However, this relationship does not extend itself to training with all types of tasks.…”
Section: Evidence Againstmentioning
confidence: 99%
“…Adult neurogenesis is confined to brain regions with a high degree of plasticity, suggesting that these neurons may provide a means for encoding new information (for review, see Aimone et al, 2006;Leuner et al, 2006;Lledo et al, 2006;Bruel-Jungerman et al, 2007). Consistent with a role in memory formation, several studies have reported correlative evidence that survival of newborn hippocampal neurons is enhanced by tasks requiring the hippocampus Leuner et al, 2004;Olariu et al, 2005). Conversely, reduction in neurogenesis by a cytostatic agent or irradiation impairs associative hippocampal-dependent learning (Shors et al, 2001(Shors et al, , 2002Snyder et al, 2005;Saxe et al, 2006;Winocur et al, 2006).…”
Section: Introductionmentioning
confidence: 99%